1997
DOI: 10.2323/jgam.43.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of phenylalanine by ruminal bacteria, protozoa, and their mixture.

Abstract: An in vitro study was conducted to examine the metabolism of phenylalanine (Phe) by mixed rumen bacteria (B), mixed rumen protozoa (P), and a combination of the two (BP). Rumen microorganisms were collected from fistulated goats fed lucerne cubes (Medicago sativa) and a concentrated mixture twice a day. Microbial suspensions were anaerobically incubated at 39°C for 12 h. Phe and some other related compounds in both supernatants and microbial hydrolysates of the incubations were analysed by HPLC. The net degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
17
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 34 publications
9
17
1
Order By: Relevance
“…In tryptophan metabolism by rumen B, the production of skatole from indoleacetic acid was completely inhibited by SL, and no tryptophan was found to be produced from indoleacetic acid in the supernatants of the P suspensions with or without SL as reported by Okuuchi et al (1993). The observations of Allison (1965) and Kristensen (1974) reporting the production of Phe from PAA by rumen bacteria were again confirmed in this experiment, though it was also confirmed in our previous study (Amin and Onodera, 1997a). On the other hand, the production of Phe from PAA was shown to be enhanced by B 6 in all the microbial suspensions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In tryptophan metabolism by rumen B, the production of skatole from indoleacetic acid was completely inhibited by SL, and no tryptophan was found to be produced from indoleacetic acid in the supernatants of the P suspensions with or without SL as reported by Okuuchi et al (1993). The observations of Allison (1965) and Kristensen (1974) reporting the production of Phe from PAA by rumen bacteria were again confirmed in this experiment, though it was also confirmed in our previous study (Amin and Onodera, 1997a). On the other hand, the production of Phe from PAA was shown to be enhanced by B 6 in all the microbial suspensions.…”
Section: Discussionsupporting
confidence: 79%
“…Phe was converted mainly to PAA, and the production of PAA in B, P and BP suspensions with and without SL and B 6 is shown in Table 3. PAA production from Phe was almost similar to results reported previously (Amin and Onodera, 1997a). In B suspensions without additives, 187 and 284 µmol/g MN (163 and 254 µM) of Phe were converted to PAA, while the production of PAA in the suspensions with SL was inhibited (pϽ0.05) by 70.0 and 72.5% during the 6 and 12 h incubation periods, respectively.…”
Section: Effects Of Salinomycin and Vitamin B 6 On The Metabolism Of supporting
confidence: 76%
“…Thus, it is necessary to clarify whether Tyr or its precursor (HPA) can be produced from Phe by rumen microorganisms. Phe has been shown to be deaminated and converted to PAA by rumen bacteria (Van Den Hende et al, 1964;Amin and Onodera, 1997a), rumen protozoa (Coleman, 1967;Amin and Onodera, 1997a) and mixed rumen microorganisms (Patton and Kesler, 1967;Martin, 1973;Amin and Onodera, 1997a). During the studies with [U-14C]L-Phe, Scott et al (1964) observed that most of the radioactivity was present in PAA and slight activity was found in phenylpropionic acid (PPA) and benzoic acid (BZA).…”
Section: Introductionmentioning
confidence: 99%
“…There is few information about the production of Tyr from Phe by rumen microorganisms. In the study of Phe metabolism by rumen bacteria and protozoa, a relatively large amount of an unknown compound was detected at the same retention time as Tyr on the chromatograms of HPLC (Amin and Onodera, 1997a). However, the compound was not identified as Tyr because the peak of Tyr overlapped with p-hydroxyphenylacetic acid (HPA) by the HPLC method (Amin et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation